FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN PADA PRODUK MAKANAN KUCING (Studi Kasus Toko Ki Petshop Di Kota Padang Panjang) - Indah Febriyani; Zuwardi (Jurnal Ekonomi dan Bisnis, 2025)
This research is motivated by consumers' lack of attention to product quality when purchasing cat food products and consumers who only want to buy cheap prices which can make their pets unhealthy. Apart from that, the availability of cat food products is still not very complete at Ki Petshop stores, which makes consumers switch to other stores. And when purchasing products, consumers still consider or compare prices at Ki Petshop stores compared to other stores. This type of research uses field research, namely conducting research by going directly into the field to obtain data using a quantitative approach. As a result of the analysis carried out using SPSS 24, the research results showed that (1) product quality had a significant effect on purchasing interest where the value of Tcount (2.162) ≥ Ttable (1.985) and the significance level was 0.003 ≤ 0.05. (2) product availability has a significant effect on purchasing interest where the value of Tcount (1.990) ≥ Ttable (1.985) with a significance level of 0.001 ≤ 0.05. (3) price has a significant effect on buying interest where Tcount (6.820) ≥ Ttable (1.985) with a significance level of 0.000 ≤ 0.05. (4) product quality, product availability and price with a Fcount value of 44.611 ≥ Ftable 2.70 with a significance level of 0.000 ≥ 0.05 and the coefficient of determination test results obtained were 0.593 or 59.3% so it can be concluded that the product quality variable, Product availability and price influence purchasing interest by 59.3% and the remaining 40.7% is influenced by other variables.